Knowledge Management and the Performance of Small and Medium Enterprises in Nigeria - Ibidunni, A. S.; Mbamali, W.; Olaniyi, K. (Covenant Journal of Entrepreneurship, 2022)
Existing studies in the knowledge management domain has shown little empirical linkages with performance of small and medium enterprises (SMEs) sector of developing economies, especially from the competency and innovation perspectives. Yet, these aspects are critical to sustaining SMEs’ competitiveness in these economies. This study, therefore, seeks to examine the link between knowledge management and performance of SMEs in Nigeria. A sample size of 286 respondents was determined for this research. The regression results revealed that knowledge management dimensions significantly influenced SMEs’ performance. Consequently, the study recommends that Mangers should ensure that the firm has a knowledge management policy and or strategy for acquiring knowledge about customers, competitors, intermediaries via reading and searching for new information on the internet/in newspapers/books. In addition, training programs and conferences should be organized for employees where qualified members and external experts are invited to speak about their beliefs, values and culture at various organizational functions which will lead to improved processes in the organization.